(untitled) (Journal of the College of Basic Education, 2022)
This research (descriptive-historical) sheds light on the city of Baghdad (Dar al-Salam) in the Abbasid era (750-1258 AD) since it was built by the Caliph Abu Jaafar al-Mansur in the year (762 AD) and how he chose it as the capital of the Abbasid state, with mentioning its most important characteristics, advantages and advantages. It has a prominent position in the development and prosperity of the scientific, intellectual and cultural aspects in general, and the lyrical and musical aspects in particular. After that, the researcher reached a set of results and concluded his research with a list of sources and references.